Wyboista droga do niepodległości – Wietnam w latach 1940–1945 - Benken, Przemysław (Pamięć i Sprawiedliwość, 2015)
The Bumpy Road to Independence – Vietnam in 1940–1945The purpose of the article is the presentation of the most important facts concerning the situation in Vietnam in 1940–1945 with particular focus on the independence efforts ofthe population of that country ended in a partial success in the form of proclamation of theDemocratic Republic of Vietnam in September 1945. The text includes, among others, the geopolitical importance of the French Indochina in the context of the War on the Pacific,the policies of the colonial administration, Japan’ s activities aimed at taking the control over Vietnam, the activity of the local communist movement and the role of the UnitedStates in setting in motion the process of decolonisation of the Indochinese Peninsula.